MENUMBUHKAN KARAKTER PEDULI SOSIAL MELALUI KEGIATAN EKSTRA-KURIKULER - Moh Masduqi (Institut Keislaman Abdullah Faqih Gresik, 2020)
Abstract: The influence of the age of technology has resulted in the younger generation being more indifferent to the environment. The emergence of various technological advances, such as gadgets and online games, causes a person to lose his sense of caring and tend to be individualistic, thus creating various social problems. In such a situation, the writer is interested in an elementary education institution MI Sendang Drajat, Jambon, Ponorogo that is actively caring for and fostering social care attitudes of its students through extra-curricular activities, namely tahlil activities. The focuses of this study are: 1) what values of social care are found in the extra-curricular activities of tahlil students in MI Sendang Drajat? 2) How is the process of growing social care characters carried out at MI Sendang Drajat through this tahlil activity? The type and approach in this research is qualitative in which the data are in the form of words or pictures and the results of interview scripts, field notes (observations) and documents based on field conditions. This data will be analyzed using qualitative methods to draw conclusions. From the analysis of the data collected it can be concluded that: 1) The values of social care contained in tahlil activities in MI Sendang Drajat are the social values of togetherness, compassion (tenderness), help, help, discipline, civilized attitude, and empathy for others, 3) In the process of instilling the values of social care for students in MI Sendang Drajat, at least the teacher applies three methods or strategies, namely through routine daily or weekly activities, spontaneous activities such as visiting friends or takziah, and through exemplaryKeyword: Education, character, values, extra-curricular